Pengaruh Media Pembelajaran Monopoli Terhadap Hasil Belajar Matematika Peserta Didik Kelas IV SDN Wringinharjo 02 - Nabilahsari, Putri; Isnaati, Pebri; Riyadi, M. Ilham Rahmani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to determine the effect of using monopoly learning media on the mathematics learning outcomes of fourth-grade students at SDN Wringinharjo 02. This study uses a quantitative approach with a pre-experimental research type. The chosen research design is one group pre-test and post-test, with data collection instruments in the form of test questions given before and after the treatment. Based on the results of the study entitled